2020
DOI: 10.1007/s00467-020-04712-2
|View full text |Cite
|
Sign up to set email alerts
|

Prematurity, perinatal inflammatory stress, and the predisposition to develop chronic kidney disease beyond oligonephropathy

Abstract: Prematurity and perinatal stress, such as intrauterine growth restriction (IUGR) and chorioamnionitis, are pathological processes creating an impaired intrauterine environment. These intrauterine factors are associated with the development of proteinuria, hypertension, and chronic kidney disease (CKD) later in life. Initially, this was thought to be secondary to oligonephropathy, subsequent glomerular hypertrophy, and hyperfiltration, leading to glomerulosclerosis, a further decrease in nephron number, and fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…Some children born from complicated pregnancies have already been suffering from severe diseases, such as asthma [31,32], pulmonary hypertension [33][34][35], diabetes mellitus [36], cardiorenal metabolic syndrome [37], chronic kidney diseases [38,39], cardiovascular diseases [40], ophthalmic disorders [41], neurodevelopmental and neuropsychiatric disorders [42][43][44][45][46][47][48][49][50][51], most likely as a result of abnormal fetal programming.…”
Section: Introductionmentioning
confidence: 99%
“…Some children born from complicated pregnancies have already been suffering from severe diseases, such as asthma [31,32], pulmonary hypertension [33][34][35], diabetes mellitus [36], cardiorenal metabolic syndrome [37], chronic kidney diseases [38,39], cardiovascular diseases [40], ophthalmic disorders [41], neurodevelopmental and neuropsychiatric disorders [42][43][44][45][46][47][48][49][50][51], most likely as a result of abnormal fetal programming.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, nephron formation may not be complete in infants born prematurely, and continued nephron development with signs of abnormal morphology has been found in preterm neonates [39]. The interindividual differences in kidney development that were observed in this study suggested that early (during active nephrogenesis) postnatal exposure to an inflammatory environment [40] or nephrotoxins may play an additional role. Despite the knowledge that nephrotoxic drugs such as gentamicin or indomethacin can have disrupting effects on kidney development, they are frequently used in neonatal intensive care units [41,42].…”
Section: Perinatal Factorsmentioning
confidence: 68%
“…Extremely low birth weight (ELBW, ≤1,000 g) infants are born during active nephrogenesis, making their kidneys extremely vulnerable to damage by external factors such as exposure to nephrotoxic drugs or diseases such as neonatal sepsis. Although the development of nephrons will continue after preterm delivery, the final amount of nephrons will be less for infants who are born prematurely with an ELBW ( Faa et al, 2010 ; Abitbol et al, 2016 ; Hoogenboom et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%